The outcome of childhood adrenocortical carcinoma in Egypt: A model from developing countries. (2nd April 2020) - Zekri, Wael; Hammad, Mahmoud; Rashed, Wafaa M.; Ahmed, Gehad; Elshafie, Maged; Adly, Marwan H.; Elborai, Yasser; Abdalla, Badr; Taha, Hala; Elkinaae, Naglaa; Refaat, Amal; Younis, Alaa; et al.
Abstract: Adrenocortical carcinoma (ACC) is a rare, aggressive endocrine neoplasm. Complete surgical resection is the single most important treatment. Most available information has been learned from experience with its more frequent adult counterpart. In this study, we assessed the features and survival outcome of patients with ACC at Children's Cancer Hospital Egypt (CCHE). Patients diagnosed at CCHE between July 2007 and November 2016 were followed up on until November 2018. Patients with stages I and II were operated upon, while stages III and IV had received combinations of doxorubicin, etoposide, platinol, and mitotane (DEPM) beside the attempt to conduct surgery when feasible. Data belonging to 18 patients (7 men and 11 women) were analyzed; median age at diagnosis was 48.5 months. Sixteen patients had presented with secreting tumors. Six patients were diagnosed with stage I disease; four with stage II; three with stage III; and five with stage IV carcinoma. By the end of this study, 10 patients have survived; five-year overall survival of 66.3%. Surviving patients were all of stage I or II diseases and were all in remission. Seven patients who did not survive died due to tumor progression, while one patient died after chemotherapy. The prognosis of ACC is essentially dependent on a successful complete resection of the tumor and thus on the initial tumor stage. The mitotane and DEP protocols may help control tumor growth in the advanced stages for only short periods. Key points: Initial stage and resectability are the main indicators of outcomes in adrenocortical carcinoma. Chemotherapeutic agents used in developed countries did not achieve the same outcomes. Further molecular-pharmacology differentiation is needed for various ethnic populations.